Clinical and psycho-functional features of rehabilitants with chronic fatigue syndrome - Grygus, Igor; Nogas, Angela; Nebova, Nataliia (Journal of Education, Health and Sport, 2017)
In the last hundred years, the problem of "diseases of civilization" arose before mankind. So, in the last quarter of the last century, there were descriptions of a new disease of the civilization of the chronic fatigue syndrome. Purpose: to review the literature to identify the clinical and psycho-functional characteristics of rehabilitants with chronic fatigue syndrome. Methods of research: analysis of scientific literature, synthesis and generalization. Results: Primary symptoms and additional, basic clinical manifestations of the chronic fatigue syndrome are singled out. The features of the immune status disorder, the parameters of cellular and humoral immunity in patients with chronic fatigue syndrome are considered. Based on the analysis of the literature, the features of the psychological status of patients with chronic fatigue syndrome are examined and the prevalence of signs of socio-psychological disadaptation is presented; hypochondriacal, depressive, paranoid and other types of personality profiles. Conclusions: Patients with chronic fatigue syndrome have a number of characteristics that can affect the effectiveness of rehabilitation activities.